Population genomic data reveal genes related to important traits of quail - Wu, Yan; Zhang, Yaolei; Hou, Zhuocheng; Fan, Guangyi; Pi, Jinsong; Sun, Shuai; Chen, Jiang; Liu, Huaqiao; Du, Xiao; Shen, Jie; Hu, Gang; Chen, Wenbin; et al. (Gigascience, 2018)
Japanese quail (Coturnix japonica), a recently domesticated poultry species, is important not only as an agricultural product, but also as a model bird species for genetic research. However, most of the biological questions concerning genomics, phylogenetics, and genetics of some important economic traits have not been answered. It is thus necessary to complete a high-quality genome sequence as well as a series of comparative genomics, evolution, and functional studies. Here, we present a quail genome assembly spanning 1.04 Gb with 86.63% of sequences anchored to 30 chromosomes (28 autosomes and 2 sex chromosomes Z/W). Our genomic data have resolved the long-term debate of phylogeny among Perdicinae (Japanese quail), Meleagridinae (turkey), and Phasianinae (chicken). Comparative genomics and functional genomic data found that four candidate genes involved in early maturation had experienced positive selection, and one of them encodes follicle stimulating hormone beta (FSHβ), which is correlated with different FSHβ levels in quail and chicken. We re-sequenced 31 quails (10 wild, 11 egg-type, and 10 meat-type) and identified 18 and 26 candidate selective sweep regions in the egg-type and meat-type lines, respectively. That only one of them is shared between egg-type and meat-type lines suggests that they were subject to an independent selection. We also detected a haplotype on chromosome Z, which was closely linked with maroon/yellow plumage in quail using population resequencing and a genome-wide association study. This haplotype block will be useful for quail breeding programs. This study provided a high-quality quail reference genome, identified quail-specific genes, and resolved quail phylogeny. We have identified genes related to quail early maturation and a marker for plumage color, which is significant for quail breeding. These results will facilitate biological discovery in quails and help us elucidate the evolutionary processes within the Phasianidae family.